Going beyond the fifth child: Exploring the determinants of desire for more children among high parity partnered women in Uganda. - Godfrey Tumwizere; Yiga Joseph Douglas; Allen Kabagenyi; Betty Kwagala (PLOS Global Public Health)
Background Despite the extensive research on fertility desire among women worldwide, there is a dearth of literature on the desire for more children among high-parity women. This study aimed to identify the determinants of the desire for more children among high parity partnered women in Uganda. Methods This study was based on nationally representative data from the 2016 Uganda Demographic and Health Survey. The study sample comprised of a weighted sample of 4502 women aged 15-49 years with five and more children. A complimentary log-log model was fit to identify factors associated with the desire for more children among high-parity women in Uganda at the 5% level of significance. Results The findings revealed that 21% of high parity partnered women desired more children. The odds of desire for more children were 26% higher among women without decision-making autonomy on the number of children (AOR = 1.262 95% CI 1.109-1.415) than women with decision-making autonomy, women with preference of more than 3 boys had 2 times odds of desire for more children compared to those who preferred less than three boys (AOR = 2.021, 95% CI = 1.726-2.367) while Catholic women had 80% higher odds of desire for more children (AOR = 1.896, 95% CI = 1.786-2.020) compared to Anglicans. On the other hand, the odds of having a desire for more children were 33% lower among Muslims (AOR = 0.676, 95% CI 0.559-0.817) and 21% lower among Pentecostals (AOR = 0.70895% CI = 0.598-0.837) compared to Anglicans. The odds of having a desire for more children were 75% lower among women with primary education (AOR = 0.252, 95% CI 0.062-0.441) than among those with no education. Compared to women using modern contraceptives the odds of desire for more children were 38% lower (AOR = 0.620, 95% CI 0.481- 0.865) than those with not using modern contraceptives. Women with at least five living children had 75% lower odds of desire for more children (AOR = 0.255, 95% CI 0.060-0.549) compared to those with two living children. Women with primary education had 75% reduced odds of desire for more children compared to no education (AOR = 0.252 95% CI 0.062-0.441) while women whose husbands attained at least a secondary level of education had 79% reduced odds of desire for more children (AOR = 0.210, 95% CI 0.190-0.411) compared to women whose husbands had no education. Conclusions This study recommends that Uganda's policymakers and Programme implementers emphasize the attainment of secondary or higher education, collaborate with religious leaders to promote health education sensitive to religious beliefs and practices and empower women to challenge social norms that restrict women's decision-making autonomy on fertility.